Teachers’ Perception in Google Forms-Based English Assessment in An Indonesian Vocational High School - Musdalifah Yakkop; Muhammad Basri; Murni Mahmud (Pascasarjana Universitas Negeri Makassar, 2021)
The use of ICT for learning evaluation is important. Today, Google Forms is a paperless-based system that is widely used for learning evaluation. The significant implication of using Google Forms as an assessment tool is that it can lighten the workload for teachers. This study is qualitative research with a case study approach. This research aims at finding out the teachers' perception of Google forms-based application in the EFL classroom. This research was conducted at SMK Muhammadiyah 3 Makassar. The subject of the research is three English teachers who use Google Forms-based applications in the EFL classroom. The instruments used were observation, interviews, and documents. This research found that The teachers' perception of Google forms-based application in assessing English is classified into two categories namely highly and moderately perceived on Google forms-based application in assessing English. Besides that, the positive features of the Google forms as an EFL assessment tool is considered more efficient, practical, simple, and save more time, money, and energy.